2020
DOI: 10.1007/s42770-020-00251-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Shiga toxin-producing Escherichia coli with leafy green vegetables

Abstract: Shiga toxin-producing Escherichia coli (STEC) are important foodborne pathogens responsible for a wide spectrum of diseases including diarrhea, bloody diarrhea, and hemolytic uremic syndrome (HUS). A considerable number of outbreaks and sporadic cases of HUS have been associated with ingestion of fresh ready-to-eat products. Maintenance and persistence of STEC in the environment and foods can be related to its ability to form biofilm. A non-O157 STEC strain isolated from bovine feces was distinguished by its g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The preponderance of raw beef and hamburger meat as a source of contamination seems to have declined nowadays in favor of fresh products such as leafy greens, lettuce [ 50 ], or sprouts [ 12 , 70 ], which are now recognized as the second most common source of foodborne transmission [ 71 ]. In comparison to O157 E. coli , non-O157 strains display enhanced biofilm formation attributes as well as increased adherence to green leaves, which may account for the rising role of these strains [ 72 , 73 ]. In France, contaminated raw milk cheese consumption was the source of a major outbreak in 2018, and this argues for the avoidance of non-pasteurized cheese in children under six years of age [ 45 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The preponderance of raw beef and hamburger meat as a source of contamination seems to have declined nowadays in favor of fresh products such as leafy greens, lettuce [ 50 ], or sprouts [ 12 , 70 ], which are now recognized as the second most common source of foodborne transmission [ 71 ]. In comparison to O157 E. coli , non-O157 strains display enhanced biofilm formation attributes as well as increased adherence to green leaves, which may account for the rising role of these strains [ 72 , 73 ]. In France, contaminated raw milk cheese consumption was the source of a major outbreak in 2018, and this argues for the avoidance of non-pasteurized cheese in children under six years of age [ 45 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…In this context, in the USA serogroups O26, O45, O103, O111, O121, and O145 (also known as "the big six"), alongside O157 have been considered adulterants in raw, non-intact ground beef products since 2011 [13]. Nevertheless, the presence of STEC in soil, water, and animal manure are factors associated with the contamination of other foods such as vegetables [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The most studied serovar from pathogenic E. coli is O157:H7, which harbors genes that encodes for the Shiga toxin, and it could produce hemolytic uremic syndrome in humans. However, it has also been described that non‐O157 E. coli strains, can also cause diarrheal infections and hemolytic uremic syndrome in humans by auto‐transported proteins (Abe et al, 2020). In produce, it has been reported that STEC serovar O157:H7 can adhere to carrots and cilantro in different manners; in the study, E. coli O157:H7 shows a recovered average between 3.7 log 10 and 4.3 log 10 viable cells from carrots and cilantro, respectively (Sai et al, 2019).…”
Section: Interaction Of Foodborne Pathogens With Plantsmentioning
confidence: 99%
“…Also, for the same strain it has been reported that adherence to the surface of leafy vegetables occurs through a type of fimbria known as curli, which is also involved in the formation of biofilm, since a knockout mutant in csgA , a gene involved in the formation of curli, is unable to colonize the leafy surface of lettuces (Fink et al, 2012). Furthermore, for the strain E. coli serovar O105:H18, it has been observed that the sab gene is partially required for the adherence of this strain to the surface of rocket leaves (Abe et al, 2020). In contrast, in lettuce roots from Valerianella locusta , it was observed that the genes associated to adherence and colonization, iha (enterobactin siderophore receptor) and hcpA (pilin subunit of type IV pilus), are not involved in the adhesion from EHEC O157H7 strain Sakai (wild type [WT]), since isogenic mutant strains in those genes do not show reduced adhesion, compared to what was observed with the WT strain, to lettuce roots (Eissenberger et al, 2018).…”
Section: Interaction Of Foodborne Pathogens With Plantsmentioning
confidence: 99%